Crossing borders with youth arts in a remote Australian community. Issue 1 (2nd January 2016) - Lee, Kathryn
Abstract: This paper draws on the personal experience of the author who had been employed as a Youth Arts Manager in a small, desert town in the Northern Territory. In her research honours study during the project for which she was engaged, she aimed to understand the tensions she experienced managing this partnership. Now, five years later, she reconsidered the experience and, placing the concept of culture shock at the forefront of her perspective, came to see the experience in a new light. Kate proposes that understanding protocols is a process embodiment that may be affected by the experience of culture shock, and secondly, that creative processes can be reduced neither to process nor product. Rather, with a clear understanding of aims and objectives as they relate to context, from community development can fruitful artistic partnerships.